Detection of composition of functional component theabrownins in Pu-erh tea by degradation method - Simin Hu; Xiaolei Li; Chuangchuang Gao; Xianyu Meng; Mingchao Li; Yuqian Li; Tianrui Xu; Qian Hao (Food Science and Human Wellness)
Habitual tea consumption can reduce the risk of ASCVD morbidity and mortality and all-cause mortality in China, and long-term adherence to this habit can provide greater protection. Pu-erh tea is one of the representatives of post-fermented teas, and the polymers in Pu-erh tea have anti-cancer and anti-hyperlipidemic activities, but their chemical composition is still unknown. In this study, the chemical composition of Pu-erh tea was investigated in detail and eight (1–8) known compounds were isolated. The polymers in Pu-erh tea were also degraded by thiol degradation, and the fragments of quercetin and (–)-epicatechin-3-O-gallate were found in the thiol degradation products of Pu-erh tea polymers by UPLC observation and separation and purification. This is the first time that this fragment was obtained in Pu-erh tea polymer.